OPTIMASI PAREMETER PENGELASAN SMAW TERHADAP HASIL UJI TARIK MENGGUNAKAN METODE TAGUCHI PADA POSISI 3G - Lukman, Muhammad; Hamid, Abdul; Nailul Ulum, Muhammad Showi (Journal of Mechanical Engineering and Applied Technology, 2025)
This research aims to optimize the Shielded Metal Arc Welding (SMAW) process parameters on tensile strength using the Taguchi method in the 3G welding position. The study investigates the effects of welding current, electrode type, and electrode soaking time on the quality of weld joints. The base material used was ASTM A36 steel, welded with E7016 and E7018 electrodes at current settings of 85 A and 95 A. The experimental design employed a Taguchi L4 (2³) orthogonal array, resulting in four parameter combinations. Performance analysis used the Larger is Better Signal-to-Noise (S/N) ratio approach. The optimum parameter combination was found at 85 A welding current, E7016 electrode, and 30 minutes of electrode soaking, achieving a maximum average tensile strength of 404.35 MPa. Analysis of Variance (ANOVA) revealed that the most influential factor on tensile strength was electrode soaking time (57.65%), followed by electrode type (32.38%), and welding current (9.97%). The absence of residual error indicates a highly efficient and reliable experimental model. This study confirms that the Taguchi method is an effective approach to optimize SMAW parameters, enhance weld joint quality, and minimize trial-and-error efforts in the welding process. Keywords: SMAW Welding, Tensile Test, Taguchi Method, 3G Position, Parameter Optimization, ANOVA.